Factores de riesgo obstétricos relacionados con recién nacidos a término con APGAR bajo a los 5 minutos atendidos en el Hospital General Isidro Ayora de Loja. - Ríos Ludeña, Kristel Natalia (2017)
Knowing the condition of the newborn and its indispensable in the first hours of life. In this period, most of the adaptation problems can be detected, such as thermoregulation, alterations, respiratory distress and neurological disorders. The investigations goals was to identifying the obstetric risk that predominates in pregnant women, determinating the APGAR score according to each newborn, and link the risk factors with the APGAR score presented. This retrospective and descriptive study was carried out in the obstetrical center of the Hospital General Isidro Ayora de Loja. The universe was conformed by 224 new borns of Isido Ayora Gneral Hospital’s Obstetric Center from May to October in 2016, getting a sample of 40 term new borns, son of mothers with comorbidities and complete clinical histories. A data collection, sheet was used as a main tool, which allowed us to develop each of the objectives. With the results, it is concluded that the main factors of Obstetric risk found in the study group are hypertensive disorders with 42% (n = 17) and placental factors with 25% (n = 10). As causes of low APGAR score, in addition to the total of 40 cases studied, 67% (n = 27) of the new borns presents an APGAR low score (4-6 points), while the 33% (n = 13) presented a APGAR score less than 3 points . Finally, it was established that there is a remarkable correlation between the obstetric risk factors and the APGAR low score, mostly the arterial hypertension with 25% (n = 10), which is the main cause of the APGAR score whit less than 7 points. Key words: Hypertension, Vitality, Pregnant, Newborn.